The use of misoprostol in termination of second-trimester pregnancy - Chen-Ju Lin; Shu-Chin Chien; Chih-Ping Chen (Elsevier, 2011)
Misoprostol, a synthetic prostaglandin E1 analog, is initially used to prevent peptic ulcer. The initial US Food and Drug Administration-approved indication in the product labeling is the treatment and prevention of intestinal ulcer disease resulting from nonsteroidal anti-inflammatory drugs use. In recent two decades, misoprostol has approved to be an effective agent for termination of pregnancy in various gestation, cervical ripening, labor induction in term pregnancy, and possible management of postpartum hemorrhage. For the termination of second-trimester pregnancy using the combination of mifepristone and misoprostol seems to have the highest efficacy and the shortest time interval of abortion. When mifepristone is not available, misoprostol alone is a good alternative. Misoprostol, 400 μg given vaginally every 3-6 hours, is probably the optimal regimen for second-trimester abortion. More than 800 μg of misoprostol is likely to have more side effects, especially diarrhea. Although misoprostol can be used in women with scarred uterus for termination of second-trimester pregnancy, it is recommended that women with a scarred uterus should receive lower doses and do not double the dose if there is no initial response. It is also important for us to recognize the associated teratogenic effects of misoprostol and thorough consultation before prescribing this medication to patients regarding these risks, especially when failure of abortion occurs, is needed.